Is It Possible to Run Nature-Based Thematic Learning During Pandemic? : A Strategy of Lower Grade Teachers - Erfin Uswatun Nisa'; Hou Jiamin (Nur Science Institute, 2022)
Background: This study aims to reveal how the planning, implementation and evaluation of low grade teacher strategies in implementing nature-based thematic learning during the pandemic at Muhammadiyah Alam Surya Mentari Elementary School (MASMES), Surakarta, Indonesia. Method: The method used in this studyis descriptive qualitative with a case study design. The nine informants recruited consisted of three lower grade teachers, three parents and three students. The techniques used in this studyare interviews and documentation. Data were analyzed by data reduction, data presentation, and drawing conclusions. The data validity technique is technique triangulation and source triangulation. Result: The results of this study showed that (1) The strategic planning of low-grade teachers in the implementation of nature-based thematic learning during the pandemic has been carefully structured, but there are several obstacles. At this planning stage, it is carried out systematically. (2) The implementation of low grade teacher strategies in implementing nature-based thematic learning during the pandemic has been going well, but there are obstacles in the learning process. (3) The evaluation in this study has been going well, but there are some obstacles in it. There is a follow-up in the form of improvement so that for future activities such problems do not occur. Various ways to find solutions have been carried out so that they can be used as benchmarks or references in the future so that they are even better. Novelty: This study reveals the strategies of low grade teachers in implementing nature-based thematic learning during a pandemic in elementary schools.